BE631688
<PICT:0938915/III/1> <PICT:0938915/III/2> <PICT:0938915/III/3> <PICT:0938915/III/4> <PICT:0938915/III/5> <PICT:0938915/III/6> <PICT:0938915/III/7> A dendritic seed is pulled from a supercooled portion of a melt, the supercooled portion having a surface area of at least 1,6 cm2, at a rate of 0,63-10 cm, so as to produce a dendritic body comprising two or more parallel dendritic crystals, each crystal being joined to the adjacent crystal by a thin web of substantially uniform thickness extending over the entire length of the body. The parallel dendritic crystals may have a thickness of 0,05-0,625 mm. and a width of 0,5-5 mm. The web may have a thickness of 0,0025-0,075 mm. and a width of 12,5 mm. The seed may have three interior twin planes; and may be a single dendritic crystal (Fig. 2) or a portion of a grown body comprising two or more parallel dendritic crystals with or without an intermediate web (Figs. 6 and 5, respectively). The web of the resulting dendritic body may contain no interior twin planes (Fig. 9) or one thereof (Fig. 10 or 11). The melt may be of silicon, germanium, zinc selenide or sulphide, or a compound of aluminium, gallium, or indium with antimony, arsenic, or phosphorus. A semi-conductor material may be intrinsic or n- or ptype. Induction, radiation, or electron beam heating may be employed. Pulling may be effected in a vacuum or a protective atmosphere of argon, helium, hydrogen, or nitrogen. As shown in Fig. 1, a dendritic body 26 is pulled from a melt 18 in a crucible 19 having a quartz lining and an apertured cover 22 of molybdenum, tantalum, or tungsten. Crucible 19 is surrounded by a quartz heat shield 37, glass enclosure 32, and induction heating coil 20. Specifications 889,058 and 913,674 are referred to.